2020
DOI: 10.3390/microorganisms8121896
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Global Transcriptomic Response to Oxidative Stress of Bacillus anthracis htrA-Disrupted and Parental Wild Type Strains

Abstract: We previously demonstrated that the HtrA (High Temperature Requirement A) protease/chaperone active in the quality control of protein synthesis, represents an important virulence determinant of Bacillus anthracis. Virulence attenuation of htrA-disrupted Bacillus anthracis strains was attributed to susceptibility of ΔhtrA strains to stress insults, as evidenced by affected growth under various stress conditions. Here, we report a comparative RNA-seq transcriptomic study generating a database of differentially e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…MazG belongs to the all-α NTP pyrophosphatases (Galperin et al, 2006), which exist from viruses and bacteria to humans (Song et al, 2015;Rihtman et al, 2019;Zaide et al, 2020;Huang et al, 2021;Wood et al, 2021;Han et al, 2022). As a housecleaning enzyme, MazG functions at the cell nucleotide metabolism by degrading the non-canonical NTPs, preventing mutagenesis and DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MazG belongs to the all-α NTP pyrophosphatases (Galperin et al, 2006), which exist from viruses and bacteria to humans (Song et al, 2015;Rihtman et al, 2019;Zaide et al, 2020;Huang et al, 2021;Wood et al, 2021;Han et al, 2022). As a housecleaning enzyme, MazG functions at the cell nucleotide metabolism by degrading the non-canonical NTPs, preventing mutagenesis and DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…As a housecleaning enzyme, MazG functions at the cell nucleotide metabolism by degrading the non-canonical NTPs, preventing mutagenesis and DNA damage. Moreover, MazG helps bacteria in response to oxidative stress in E. coli (Han and Eiteman, 2018), B. anthracis (Zaide et al, 2020), and Mycobacterium (Shi et al, 2019). In addition, many studies show that MazG is critical in regulating the DNA damage response in mycobacterium (Lu et al, 2010;Lyu et al, 2013;Fan et al, 2018;Shi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, one previous study showed that deleting htrA did not appear to affect the level of PA produced in the Sterne strain [ 30 ]. Since HtrA can play a regulatory role and affect the expression of more than 1000 genes [ 31 ], and its effect on secretory proteins is obviously different in various media conditions [ 32 ], it is speculated that knockout of htrA plus other protease gene or genes may cause complex regulatory mechanisms such as compensatory protein degradation under the culture condition of our study. Nevertheless, the detailed reason for this phenomenon remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Prokaryotic HtrAs play an essential role in bacterial virulence and survival under cellular or environmental stress [ 10 , 11 , 12 , 13 , 14 , 15 ]. Plant HtrAs maintain the photosynthetic machinery by acting as a chaperone in the assembly of photosystem II and as a protease in the degradation of photo-damaged reaction centres [ 2 ].…”
Section: Introductionmentioning
confidence: 99%